Dnmt3a is downregulated by Stat5a and mediates G0/G1 arrest by suppressing the miR-17-5p/Cdkn1a axis in Jak2V617F cells - Jie Zhou (BMC, 2021)
Abstract Background Despite of the frequently reported Dnmt3a abormality in classical myeloproliferative neoplasms (cMPNs) patients, few research explores how the Dnmt3a is regulated by Jak2V617F mutation. In this study, we have investigated how the Dnmt3a is regulated by Jak2V617F mutation and its effects on downstream signaling pathways in cMPNs. Methods Specimens of Jak2V617F positive cMPN patients and normal controls were collected. Murine BaF3 cell line was used to construct cell models. Dual-Glo luciferase assays and chromatin immunoprecipitation (ChIP)-qPCR were performed to detect the impact of Stat5a on transcription activity of Dnmt3a. Soft agar colony formation assay and cell counting assay were performed to detect cell proliferation. BrdU staining and flow cytometry were used to investigate cell cycle distribution. Western blotting and quantitative reverse-transcription PCR (qPCR) were performed to detect the expression levels of genes. Results Firstly, the results of western blotting and qPCR revealed that compared with the control samples, Dnmt3a is downregulated in Jak2V617F positive samples. Then we explored the mechanism behind it and found that Dnmt3a is a downstream target of Stat5a, the transcription and translation of Dnmt3a is suppressed by the binding of aberrantly activated Stat5a with Dnmt3a promoter in Jak2V617F positive samples. We further revealed the region approximately 800 bp upstream of the first exon of the Dnmt3a promoter, which includes a gamma-activated sequence (GAS) motif of Stat5a, is the specific site that Stat5a binds to. Soft agar colony formation assay, cell counting assay, and BrdU staining and flow cytometry assay found that Dnmt3a in Jak2V617F-BaF3 cells significantly affected the cell proliferation capacity and cell cycle distribution by suppressing Cdkn1a via miR-17-5p/Cdkn1a axis and mediated G0/G1 arrest. Conclusions Transcription and translation of Dnmt3a is downregulated by the binding of Stat5a with Dnmt3a promoter in Jak2V617F cells. The GAS motif at promoter of Dnmt3a is the exact site where the Stat5a binds to. Dnmt3a conducted G0/G1 arrest through regulating miR-17-5p/Cdkn1a axis. The axis of Stat5a/Dnmt3a/miR-17-5p/Cdkn1a potentially provides a treatment target for cMPNs.